Distribution, sources, and health risk assessment of polycyclic aromatic hydrocarbons in dust from urban environment in the Niger Delta, Nigeria. Issue 3 (2nd April 2016) - Iwegbue, Chukwujindu M. A.; Obi, Grace
ABSTRACT: The concentrations of the 16 U.S. Environmental Protection Agency polycyclic aromatic hydrocarbons (PAHs) were measured in urban street dust with a view to understanding the potential risk to urban residents exposed to street dust, sources, and distribution of the PAHs. Gas chromatography–mass spectrometry was used to measure the concentrations of the PAHs after ultra-sonication with hexane/dichloromethane and clean up. The total concentrations of the Ʃ16 PAHs in the urban street dust from Warri and its environs ranged from 165.1 to 1012 µg kg −1 . The isomeric ratios and the PCA indicated that combustion of petroleum and biomass are the major sources of PAHs in Warri and its environs. The total BaP carcinogenic and mutagenic potency concentrations (ƩBaPTEQ and ƩBaPMEQ ) were in the range of 0.03 to 219 µg kg −1 and 0.52 to 182 µg kg −1, respectively. The incremental life cancer risk from exposure of the residents of Warri and its environs ranged from 4.07 × 10 −7 to 3.11 × 10 −3 and 2.13 × 10 −7 to 1.49 × 10 −3 for the children and adults, respectively, which were higher than the baseline value of acceptable risk of 10 −6 ( i.e ., one case per million people).